Strategi Pengembangan Urban Farming di Kelompok Tani Cempaka, Kota Jakarta Selatan - EFRIYANTI, NOVI; DEWI, RATNA KOMALA; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023, 2023)
Urban Farming Development Strategy in Cempaka Farmers Group, South Jakarta City The increase in population and the high demand for agriculture have made urban farming an urgency that must be developed by urban communities. Urban farming activities in the Cempaka Farmer Group require an appropriate strategy formulation in order to develop. The purpose of this study is to identify internal and external factors, then alternative strategies and determine priority strategies for urban farming development in Cempaka Farmers Group, South Jakarta City. Priority strategies are obtained through matrix analysis of IFE, EFE, SWOT, and QSPM. The results of the analysis obtained on internal factors, the main strength in farmer groups is that they already have the group's vision and mission (0.197). The main weakness is that the production of urban farming is still lacking and many are not worth selling (0.083). On external factors, the main opportunity is the existence of government assistance in the form of programs, training, and agricultural tools for urban agriculture actors (0.370). The biggest threat is agricultural land that does not belong to the Cempaka Farmer Group (0.164). Based on the results of the priority analysis of the chosen strategy, namely carrying out activities in farmer groups to the maximum with the help of outside parties, the government, and currently developing technology.